Simulasi Pemodelan Sistem Eksitasi Statis pada Generator Sinkron terhadap Perubahan Beban - Hastuti Azis; Pawenary Pawenary; Meyhart Torsna Bangkit Sitorus (Sekolah Tinggi Teknik PLN, 2019)
Excitation system is one of the most important parts of synchronous generators, where the system functions to provide dc power to the field generator coil. Iin this study, a static excitation system consisting of transformers and connected thyristors in bridge configuration has been implemented in synchronous machines that operate as 206,1 mva capacity generators, 16,5 kv using the help of matlab simulink r2017b software. By adjusting the load given to the generator, variations in excitation currents can affect the amount of output voltage generated by the generator so that it can increase and decrease the induced voltage. In full load conditions, namely p = 175 mw, q = 100 mvar, the results of the study show that when the simulation is run at alpha 0 °, it is known that the average value of dc voltage is 496,4 v, excitation current is 1057 a and voltage generator output has increased beyond its nominal voltage of 16,72 kv. in this case, to maintain the terminal voltage, the excitation current must be reduced by increasing the angle of shooting of the thyristor to an alpha angle of 45 °, so that the average dc voltage can be reduced to 479,3 v, as well as the excitation current to 985,9 a. the generator output voltage at the alpha 45 ° angle is obtained according to its nominal value of 1,.5 kv.